Optimization finding prime numbers in C++ - Alibiуev, D.B.; Seksembayeva, M.A. (Bulletin of the Karaganda University. Mathematics Series, 2015)
In this article discusses ways to optimize for finding prime numbers using the Sieve of Eratosthenes algorithm, Miller-Rabin test and using an algorithm BPSW. In the work shows the results of the programs, where searching for prime numbers, such as a maximum for N = 2*1010. Also in the work shows programs in C++ optimized by time or by use memory. The results were reflected in the tables and as a graph for each of the considered algorithm.